The Effect of Mind Mapping on the Tenth Graders’ System Thinking on Trophic Structure Topic - Achmad Fanji Alhusein; Meilinda Meilinda; Ratu Mutiara Wulandari (Jurnal Penelitian Pendidikan IPA, 2023)
Students’ inability to understand the concept of science holistically has been identified in several studies on students’ difficulty to understand the relationship between levels of organization of life. It is because of the reduced teaching and learning process in Biology in which the actual learning topics are taught separately without the attempt to connect the various topics. This study was aimed at reporting the thinking skills of high school students after being exposed to learning activities involving mind mapping note-taking on water cycle topics. It is a Quasi-Experimental study with a Nonequivalent Control Group Design and simple Random Sampling. The data were collected by means of essay test and questionnaire. For homogeneous and normally distributed data, the result of paired t-test showed a significant difference in the data (0.795). Furthermore, for not normally distributed data, they were analyzed using the Mann-Whitney test. The average of test results was 69.47 for the experimental class and 66.12 for the control class.